Climate and the Amazon (Orinoquia, 2007)
Titulo en español: Clima en el AmazonasSummary: When concerning ourselves with the future of the earth’s climate we must not make the grave mistake of counting only the quantities of carbon dioxide released into the atmosphere from the combustion of fossil fuels, while neglecting those from changes in vegetation cover. But, there is another crucial dimension too: the role of natural ecosystems in giving us a climate we can live with. In this context the future of the Amazon forest is absolutely vital.